A systematic review and meta-regression of exogenous ketone infusion rates and resulting ketosis—A tool for clinicians and researchers - Storoschuk, Kristi L.; Wood, Thomas R.; Stubbs, Brianna J. (Frontiers in Physiology, 2023)
Introduction: Ketone bodies such as beta-hydroxybutyrate (BHB) have pleiotropic functional benefits as fuel and signaling metabolites and may have multiple clinical applications. An alternative to inducing ketosis by dietary modification is intravenous delivery of exogenous sources of ketones. It is unknown whether there is a strong relationship between BHB infusion rate and blood BHB concentrations in the published literature; this information is vital for clinical studies investigating therapeutic effects of ketosis. This systematic review aimed to aggregate available data and address this gap. Methods: The PubMed and EMBASE databases were searched, and data were extracted from 23 manuscripts where BHB was infused and maximum and/or steady state BHB levels assessed. Infusion rate was adjusted when racemic BHB was infused but only ᴅ-BHB was measured. Results: Using a random effects meta-regression, strong linear relationships between BHB infusion rate and maximal (y = 0.060 + 0.870x, R2 = 87.2%, p<0.0001) and steady state (y = -0.022 + 0.849x , R2 = 86.9%, p<0.0001) blood BHB concentrations were found. Sensitivity analysis found this relationship was stronger when studies in non-healthy populations were excluded (y = 0.059 + 0.831x, R2 = 96.3%, p<0.0001). Conclusions: There is a strong relationship between BHB infusion rate and blood BHB concentrations; the regressions described here can be used by clinicians or researchers to determine ketone delivery required for a target blood concentration.